Why Do Student Perceptions of Teachers’ Condemning of the Bullying and Empathy-Raising Lead to Intention to Stop Bullying? The Role of Emotions - Johander, Eerika; Turunen, Tiina; Garandeau, Claire F.; Salmivalli, Christina (Springer Science and Business Media LLC, 2026)
Two strategies used by teachers in targeted antibullying interventions, condemning of the bullying behavior and empathy-raising, have been shown to positively predict bullies' intention to stop bullying. However, the mechanism through which they work remains unknown. We tested whether moral emotions (guilt and shame), and empathic emotion (sadness) mediated the effects of students' perceptions of teachers' condemning and empathy-raising messages on their intention to stop bullying. A normative sample of 277 seventh-grade students (Mage = 12.93, SD = 0.49; 47% female) was asked to imagine having bullied a peer and being invited to a discussion with a teacher. They saw a video vignette with one of three messages: condemning, empathy-raising or a combination of both. Analyses revealed that the effects of perceived condemning of the bullying behavior on intention to stop were primarily mediated by feelings of guilt, while the effects of perceived empathy-raising were mediated by both sadness and guilt. Shame was not associated with intention to stop bullying and did not mediate the effects of the perceptions. These findings suggest that targeted anti-bullying interventions should aim to evoke guilt and sadness (or empathic concern) rather than shame.